Students’ Self-Regulated Learning based on Gender and Disciplinary Differences during Online Learning - R. D. Anazifa; K. Limiansi; A. T. Pratama (Universitas Negeri Yogyakarta, 2023)
Online learning during the pandemic has an impact on the student’s learning behavior. It altered the way students learn and manage their time. This research aims to explore students’ self-regulated learning in undergraduate students of the department of Biology Education based on gender and disciplinary differences. Research participant was distributed into female and male students. It was also distributed into two different study programs: biology and biology education. 24 questions were administered online to 124 students. The instrument consists of six sub scales, 1) goal setting, 2) environment structuring, 3) task strategies, 4) time management, 5) help seeking, and 6) self-evaluation. The relationship between students’ self-regulated learning toward gender and the relationship between students’ self-regulated learning toward study program were analyzed using independent sample T test. In addition, correlation analysis was also conducted to find the correlation between students’ self-regulated learning and students learning achievement. The results showed that there was no significant relationship between male and female students towards self-regulated learning (p = 0,665) and study programs (p = 0,008). The research results also show that there is a correlation (r = 0,0270) between student achievement and self-regulated learning.